COMPARISON OF TOTAL SERUM GLUCOSE AND CREATININE LEVELS IN DIABETES MELLITUS PATIENTS WITH COMPLICATIONS AND WITHOUT COMPLICATIONS OF CHRONIC KIDNEY DISEASE - Jannah , Shofiatul; Ardiansyah, Syahrul (PT. Antis International Publisher, 2025)
Objective: Diabetes is a chronic metabolic condition characterized by blood sugar levels that exceed the normal threshold. This increase in blood sugar levels is caused by insulin abnormalities. In diabetes mellitus, glucose and creatinine levels increase due to thickening of the basement membrane and enlargement of the glomerulus. This research used a laboratory experimental design using quantitative methods. The research subjects were Diabetes Mellitus sufferers aged over 60 years and over with a total of 30 diabetes mellitus patients accompanied by complications and 30 diabetes mellitus patients without Chronic Kidney Disease complications. The research data shows a significant value of p=0.00 (p<0.05), which means there is a comparison between the total levels of fasting blood glucose and serum creatinine in Diabetes Mellitus patients with complications and those without Chronic Kidney Disease complications.